Effects of construction methods and concrete cracking on the performance of propped diaphragm walls - Poh, Teoh Yaw. (2011)
Deep excavations in urban environments with stringent ground movement controls often require the use of diaphragm walls, and jet grouting when soft clay is encountered. Uncertainties exist in the current design and construction of diaphragm walls. Uncracked wall sections are normally considered in the analysis of wall bending moment and horizontal deflection. Ground movements associated with the trenching and the installation of the diaphragm wall are seldom considered. Also, the effects of jet grouting on the performance of the preinstalled diaphragm wall, adjacent ground and structure is not well understood. Careful studies of these aspects are important in order to enhance the deep excavation practice involving the use of diaphragm walls and jet grouting.